Massacre in Minnesota the Dakota War of 1862, the most violent ethnic conflict in American history - Anderson, Gary Clayton 1948- (University of Oklahoma Press, 2019)
"A detailed analysis of the origins, events, and aftermath of the Minnesota-Dakota War of 1862"--